The model of access for the continuous postal network management process - Unterberger Marija P.; Šarac Dragana D.; Blagojević Mladenka Z.; Vešović Predrag V. (Tehnika, 2017)
The paper has developed a dynamic, universal model for managing the access to the postal network that will provide greater demand for access service and the availability of postal network throughout the territory of the Republic of Serbia. A survey conducted in order to develop a methodology that will define the access model is presented by an algorithm through all five phases of the management process, which will enable systematic monitoring and control of all activities within the defined access model. The Post-DeSS methodology was proposed, the main objective of which was to analyze the requirements for access to the postal network and to explore the factors influencing access. The defined methodology represents one of the stages of the management process - planning, using the Delfi, Servqualand Scenario methods. Based on the achieved results obtained by the Post-DeSS methodology, guidelines for the further development of the postal network and further directions of postal market research are given.